MODERN APPROACHES TO THE TREATMENT OF HEMOLYTIC DISEASE OF THE NEWBORN - Tolipova N. K. (Modern American Journals, 2026)
Hemolytic disease of the newborn (HDN) is an immune-mediated condition caused by incompatibility between maternal and fetal blood group antigens, leading to the destruction of fetal red blood cells. This article reviews current diagnostic techniques and treatment strategies, emphasizing advances in prenatal interventions such as intrauterine transfusion and maternal immunotherapy, as well as postnatal management including phototherapy and exchange transfusion. The emerging role of artificial intelligence in improving diagnostic accuracy and treatment planning is also discussed. Despite significant progress, challenges remain in ensuring equitable access to care globally. Continued research and technological innovation are essential to enhance outcomes for affected neonates.
Keywords: Hemolytic disease of the newborn, prenatal diagnosis, intrauterine transfusion, phototherapy, exchange transfusion, intravenous immunoglobulin, artificial intelligence, neonatal care.